KEMERDEKAAN DAN KEDAULATAN RAKYAT DALAM PERSPEKTIF MOHAMMAD HATTA DAN ISLAM - Andi Andri (Sekolah Pasca Sarjana IAIN Bengkulu, 2017)
The problem in this research is 1. how is the independence and sovereignty of the people according to Mohammad Hatta? 2. How is the independence and sovereignty of the people in the perspective of Islam?3. How is the independence and sovereignty of the people according to Mohammad Hatta and the Islamic perspective?. To answer the problem of research above is done library research (library research), by using qualitative descriptive approach. The model of this research is the research of character thinking. Independence and People’s Sovereignty In Perspective Mohammad Hatta And Islam is a study that uses qualitative-inductive methods. Results of research on Independence and People’s Sovereignty In Perspective Mohammad Hatta And Islam, Declaring 1) Independence according to Mohammad Hatta that eliminates all forms of colonization of a nation. While the sovereignty of the people in his view, the ultimate power lies in the people so that the position of the people together with the king, it can be realized by way of education for the people so that people are aware of the sovereignty and will never disarm their own sovereignty, and with a clever community there will be no group that can disarm the people’s sovereignty. 2) Independence in the Islamic concept of self-liberation from ignorance, apostasy and tyranny of the ruler. While the sovereignty of the people in Islam that sovereignty lies only belonging to God alone, but in this case the people also have sovereignty which sovereignty is a deposit from God, through the sovereignty of the people that humans are entitled to choose their representatives in leading the State in order to obtain welfare for the community itself. 3) Mohammad Hatta’s concept of freedom and sovereignty of the people has a harmony with the concept of Islam related to independence at its core called independence, namely the escape of the good colony in the form of apostasy, ignorance and kezhaliman of the ruler. While the sovereignty of the people is just different from the way to see the nature of the owner of power, because in the concept of Islam the real power in a State is God. While the Sovereignty of the Community is a reflection of the power idof God.